2013
DOI: 10.1002/aur.1353
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Interaction Between Markers in GABA(A) Receptor Subunit Genes in an Argentinean Autism Spectrum Disorder Population

Abstract: Autism spectrum disorders (ASD) can be conceptualized as a genetic dysfunction that disrupts development and function of brain circuits mediating social cognition and language. At least some forms of ASD may be associated with high level of excitation in neural circuits, and gamma-aminobutyric acid (GABA) has been implicated in its etiology. Single-nucleotide polymorphisms (SNP) located within the GABA receptor (GABAR) subunit genes GABRA1, GABRG2, GABRB3, and GABRD were screened. A hundred and thirty-six Arge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…The evidence that GABRA4, associated with ASD (Ma et al, 2005), combined with GABRG2, associated with epilepsy (Haerian and Baum, 2013), are overrepresented in our sample would support this idea. This is also sustained by previous findings where a synergistic interaction between GABRB3, which is associated with ASD (e.g., Buxbaum et al, 2002), and GABRD, associated with epilepsy (e.g., Dibbens et al, 2004), was found (Sesarini et al, 2014).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The evidence that GABRA4, associated with ASD (Ma et al, 2005), combined with GABRG2, associated with epilepsy (Haerian and Baum, 2013), are overrepresented in our sample would support this idea. This is also sustained by previous findings where a synergistic interaction between GABRB3, which is associated with ASD (e.g., Buxbaum et al, 2002), and GABRD, associated with epilepsy (e.g., Dibbens et al, 2004), was found (Sesarini et al, 2014).…”
Section: Discussionsupporting
confidence: 79%
“…The MDR analysis replicated the original findings (Sesarini et al, 2014) where synergistic effect between the markers of genes GABRB3 (chromosome 15) and GABRD (chromosome 1) were associated with increased risk for autism suggesting a potential gene-gene interaction (epistasis) across chromosomes. There was no other genetic interaction in association with ASD observed for the rest of the genes studied (data not shown).…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…For example, in spite of some inconsistencies, a potential interaction between the 7-repeat allele of the DRD4 and the 10-repeat allele DAT1 has been initially reported in ADHD (for review [9]). Similarly, a recent study evaluated the independent and combined contribution of single SNPs to the genetic variance of autism spectrum disorders in an Argentinian sample and revealed a potential association of a gene-gene interaction between GABAAreceptor subunit genes with an increased risk for autism spectrum disorders [130].…”
Section: Heterogeneitymentioning
confidence: 99%